Strengthening Arabic Language Learning Through Language Environment: A Case Study in Pesantren Riau - Samin, Saproni Muhammad; Pebrian, Rojja; Alfitri, Alfitri; Supriady, Harif; Yunita, Yenni; Yasin, Mohammad Dhiya'ul Hafidh bin Fatah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
A critical gap exists between the theoretical importance of Arabic language environments in Islamic boarding schools (pesantren) and their practical implementation effectiveness. While previous research has identified various obstacles in Arabic language learning, comprehensive analysis of implementation conditions and systemic challenges in Riau Province remains underexplored. This study addresses this gap by examining Arabic language environment implementation conditions in 12 pesantren in Riau Province using qualitative exploratory case study design. Data were collected through semi-structured interviews with pesantren leaders, participant observation, and document analysis. Thematic analysis with triangulation was used for data analysis. Findings reveal a significant gap between policy and practice: 58.3% of pesantren have formal regulations but only 33.3% require full Arabic communication. Main challenges include Santri psychological factors (58.3% shyness/lack of confidence), limited competent teachers (50%), and inadequate facilities (41.7% have no supporting facilities, 0% have language laboratories). Program effectiveness is low (58.3% rate as less effective) with traditional approaches dominating (66.7% daily vocabulary memorization). However, 100% of leaders support the program and 66.7% of Santri are religiously motivated. The study recommends a holistic implementation model integrating five components: strengthening regulations, improving human resources, developing facilities, implementing communicative programs, and establishing evaluation systems. This research contributes to theoretical understanding of language environment implementation and provides practical recommendations for strengthening Arabic language programs in pesantren.